PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP PRESTASI BELAJAR SISWA (Studi Kasus Siswa Kelas VIII SMP Negeri 1 Jember Tahun Ajaran 2016/2017) - Lilis Nur Chotimah; Hety Mustika Ani; Joko Widodo (JURNAL PENDIDIKAN EKONOMI: Jurnal Ilmiah Ilmu Pendidikan, Ilmu Ekonomi dan Ilmu Sosial, 2017)
This study was conducted to determine the significant the of economic social status of parents to student achievement(Case Study On The VIII / Eight Grade Students Of SMP 1 Jember In 2016/2017 Academic Years). The method to determine the location of the research using purposive area that is at SMP 1 Jember. Determination the number of respondents in this study using simple random sampling method is 81 respondents. Methods of collection data used consisted of methods: questionnaires, interviews, observations, and documentation. Analysis of the data used is descriptive analysis and inferential analysis/statistics by using simple regression line analysis, analysis variance of the regression line, the F test, the effectiveness of the regression line, and Standard Error Of Estimate. The results showed that there was a significant effect of variables economic social status of parents to student achievement(Case Study On The VIII / Eight Grade Students Of SMP 1 Jember In 2016/2017 Academic Years)., which can be seen from the magnitude of F = 268,491> Ftable 3,112 = with a significance level of F = 0,000 < 0,05. The amount of the percentage of economic social status of parents to student achievement by 77.3%, while the remaining 22.7% influenced by other variables not examined in this study, such an interest, ingenuity, talent,intelligence , and others.